Determinación de la textura superficial por el método del circulo de arena y mediante el software SPIPtm en pavimentos asfálticos - Esparza Aguirre, Sergio Stalin (2015)
The surface layer of the pavement has an importance in the user satisfaction, the surface texture is identified as one of the factors that contribute to the slip resistance of the surface. In this paper, an experiment is described using a technique using photographs for obtaining texture values. High-end cameras allow you to capture good quality images with the aim to improve the practicality in the measurement of the texture. A method is proposed using photographs and a specialized software images. And a correlation is confirmed in the results obtained and those expressed in the NLT 335/87 standard of the sand patch.